2023
DOI: 10.1039/d2dt03646k
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and size controllable synthesis of high-quality gold nanorods using 1,7-dihydroxynaphthalene as a reducing agent

Abstract: The spectrum and size controlled synthesis of gold nanorod is of great value for its widely applicable aspect ratio-dependence property of anisotropic surface plasmon resonance. Herein, 1,7-dihydroxynaphthalene with a relatively...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…46 At the same time, the AuNR acquired from this method also shows high levels of shape yield and monodispersity. 46 As a brief summary, these research studies indicated that facile acquisition of AuNRs with a simultaneously guaranteed LSPR wavelength of beyond 1000 nm, a small diameter, and a high shape yield and monodispersity is still a great challenge. Nevertheless, it can also be inferred that the specific function pathway of different reducing agents is not fully revealed and more study is deserved.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…46 At the same time, the AuNR acquired from this method also shows high levels of shape yield and monodispersity. 46 As a brief summary, these research studies indicated that facile acquisition of AuNRs with a simultaneously guaranteed LSPR wavelength of beyond 1000 nm, a small diameter, and a high shape yield and monodispersity is still a great challenge. Nevertheless, it can also be inferred that the specific function pathway of different reducing agents is not fully revealed and more study is deserved.…”
Section: Introductionmentioning
confidence: 88%
“…Similar to many previously reported works, these results clearly reveal that firstly the increase of CTAB could facilitate the anisotropic growth of the particle that causes a decreased shape impurities and an increased rod' aspect ratio, which contributes the reagent an effect analogue to that of the silver ion. 28,30,32,46 Second, it has been discussed in the literature and our recent work that the function of CTAB in the particle anisotropic growth is based on its combination with silver ions that could significantly affect the Ag-UPD effect, of which a stronger side wall growth confinement of AuNR at a lower concentration of CTAB could result in a smaller diameter of the rod formed, and vice versa. 46,48,59 From this perspective, the slightly increased change in rod's diameter with the increment in CTAB that is opposite to that of silver ions showing a decreased change should exactly be the consequence of this mechanism.…”
Section: Effect Of Ctabmentioning
confidence: 99%
See 3 more Smart Citations